Brussels Briefing - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Brussels Briefing number 29, set out to discuss options and challenges for climate change, agriculture and food security for the future. The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) was involved in organizing the event, together with the Technical Centre for Agricultural and Rural Cooperation (CTA).